Wolność tłumacza wobec kalejdoskopu kultur na przykładzie esejów Božidara Jezernika - Cieślar, Joanna (Przekłady Literatur Słowiańskich, 2015)
The translator’s freedom in the face of the cultural kaleidoscope based on examples from Božidar Jezernik’s essays The article deals with the topic of translator’s freedom, in particular investigating the case of the translation of Jezernik’s book Kava. Zgodovina številnih zanimivih osebnosti in ovir, s katerimi se je srečevala grenka črna pijača, imenovana kava, na svojem zmagovitem pohodu iz Arabije Feliks okrog sveta, ki ga ni uspel zaustaviti niti muhtasib svetega mesta Meka which was published in Poland as a collection of essays. The author pays particular attention to the effects of the translation strategies and its relation to the essay as a literary genre. She analyzes translator’s choises on the lexical‑semantic level and shows their impact on text reception. Key words: Božidar Jezernik, essay, translation, translator